Enhancing oral reading fluency through computer assisted repeated reading / Hasimah Ja'afar ... [et al.] - Ja'afar, Hasimah; Othman, Wan Mazlini; Kesevan, Hema Vanita; M.S, Budi (2021)
This study was carried out to investigate the effectiveness of using the Computer Assisted Repeated Reading (CARR) technique to enhance Form One rural students' oral reading fluency (ORF). The single subject experimental design (SSED) involved five students who participated in a 12-week study where CARR intervention was carried out twice a week. CARR, the adaptation of the CBM/ORF procedure, was used to improve their accuracy and automatically in word decoding. Each participant's accuracy and automatically in word decoding before and after intervention were charted on line graphs. Accuracy was determined by the percentage of words read correctly. The participant's initial reading accuracy showed that they could only read at instructional level but improved after the CARR intervention. Automatically was determined by the reading rate or words read correctly per minute (WCPM) and the results too showed improvements. It can be concluded that the CARR technique was effective in improving struggling readers' reading fluency. Overall CARR can help ease teachers' burden, and their students to improve their reading skills.